Seismic reflection survey at Llancanelo region (Mendoza, Argentina) and preliminary interpretation of Neogene stratigraphic features - Osella, Ana Maria (2015)
A shallow multichannel seismic survey reaching depths of 700/800 m was performed for the first time in the Llancanelo Lake region (Southern Mendoza Province, Argentina), in order to depict the major Neogene sedimentary-volcanic sequences that form the final infilling of the tectonic-volcanic basin where the lake is located. The seismic survey advances on the results of previous geoelectric and electromagnetic surveys carried out at early stages of the research that reached the uppermost 80–100 m of the sequences (Quaternary), and therefore they go deeper in the subsoil. All the surveys were supported by surface and subsoil geological observations. After explaining the details of the performed seismic methodology, the obtained results are discussed, which indicate the presence of three major sedimentary units with increasing volcanic (basaltic layers) intercalations with depth, that accommodate to the geometry of the depocenter. The entire sequence encompasses most of the Neogene. This research sets the methodological basis for future, more detailed shallow seismic surveys in the region.